TANGGUNG JAWAB PERUSAHAAN ANGKUTAN UMUM ATAS KECELAKAAN PENUMPANG - Sugiono, Sugiono; Astutik, Sri; Amiq, Bachrul (Gapenas Publisher, 2025)
This study was motivated by the importance of legal protection for passengers as consumers of public transportation services, especially in relation to the responsibility of transportation companies in the event of an accident. The research question in this study is what form of responsibility public transportation companies have for accidents that befall passengers and what legal measures passengers can take to obtain compensation. The method used is normative juridical research with a legislative and conceptual approach. The results show that public transportation companies have full responsibility for passenger safety from departure to arrival at their destination, in accordance with Law Number 22 of 2009 concerning Road Traffic and Transportation and the Civil Code. Passengers who suffer losses due to accidents have the right to claim compensation through civil, criminal, or administrative mechanisms in accordance with the level of fault committed. Thus, the role of public transportation companies is very important in providing legal certainty, protection, and a sense of security for the community who use transportation services